Identity construction in the Barents Euro-Arctic Region – cultural cooperation as an instrument - Lagutina, Liudmila (2019)
The thesis examines how the Barents Euro-Arctic Region's identity is constructed by the means of multilateral cultural cooperation in the region. It argues that the development of a regional identity is a declared aim for the participants of Barents regional cooperation. There are also various projects in the sphere of culture which imply the realization of community-building practices aimed at Barents regional identity promotion. Therefore, it is proposed that cultural cooperation plays an important role in Barents identity construction. The issue of Barents regional identity is not a new phenomenon in the academic discourse, however, the research question of the thesis has not yet been answered. Currently, we do not know yet which role cultural cooperation plays in regional community building and collective identity development in culturally diverse regions such as the Barents Euro-Arctic Region. The research represents a multiple case-study and examines three cases at the practical level of cultural cooperation: two cultural research projects with the titles 'The Barents Region: a Transnational History of Subarctic Northern Europe' and the 'Encyclopedia of the Barents Region', and a cultural project not related to the academic sphere of cultural cooperation entitled as 'Barents Spektakel'. The analysis of the official institutional level of Barents cooperation significantly complements the study of practical-level cases. Methodologically, the thesis relies on qualitative content analysis of primary data related to the above mentioned practical cases and the official institutional level of cooperation in the region. The study has shown that cultural cooperation serves as a tool which could be significantly useful in regional identity-building practices. At the same time, it has been established that actors of cultural cooperation in the Barents Region do not perceive Barents identity construction as a primary goal of their activities. Nevertheless, Barents regional identity promotion inevitably becomes a ...